Metalliferous sediments in the Atlantis II Deep: Assessing the geological and economic resource potential and legal constraints - Christine Bertram; Anna Krätschell; Killian O'Brien; Warner Brückmann; Alexander Proelss (Kiel Institute for the World Economy (IfW), 2011)
To date, mineral resources are only mined on land but projected increases in demand have brought the exploration and exploitation of marine mineral resources back into focus. The Atlantis II Deep, located in the central Red Sea between Saudi Arabia and Sudan, is one of the largest marine sulfide deposits known, with high concentrations of metals such as zinc, copper, silver and gold. However, little is known about the economic potential of marine minerals as well as the legal constraints. Our geological assessment shows that the deep is similar in grades and scale to large land-based deposits. Its economic potential is far from negligible. The present value of possible gross revenues ranges from 3.11 to 8.21 billion US-, depending on the minerals considered. From a legal perspective, a general duty to cooperate in the exploration and exploitation of non-living resources located in disputed maritime areas is identified in both customary international law and in the UNCLOS. It is submitted that a joint development agreement is one means of ensuring compliance with this duty in general and in the case of the Atlantis II Deep in particular.
Keywords: Q30; Q34; Q38; 330; Atlantis II Deep; deep-sea mining; joint development scheme; metalliferous sediments; resource potential; Saudi-Sudanese Red Sea Commission; Meeresbergbau; Metall; Mineralische Ressourcen; Rotes Meer (Region)